Improving the Quality of Electrical Energy in the Railway Power Supply System - Sokol, Yevgen I.; Zamaruiev, Volodymyr V.; Ivakhno, Volodymyr V.; Styslo, Bohdan O. (Institute of Electrical and Electronics Engineers, 2018)
The pulsating mode of the power consumption in the railroad power supply network is the cause of the occurrence of voltage pulsations in the contact network. This leads to a decrease in the efficiency of the energy system. To compensate power fluctuations in the electric power supply network of the railway, it is proposed to use hybrid electric energy storage devices. The use of two-channel additional traction power station with an appropriate control system was proposed. The basis of the mathematical model is the data of real measurements.
Keywords: railway; power quality; BESS; two channel power station; distributed energy system; low-pass filter; separated commutation; cell equalizing; power efficiency